Does Anterior Palatoplasty Performed in Addition to Expansion Sphincter Pharyngoplasty During Multilevel Surgery Affect the Results of Surgery in OSAS Patients? - Ayşe İriz; Mehmet Düzlü; Süleyman Cebeci; Recep Karamet; Oğuz Köktürk (Gazi Medical Journal)
Objective: Multilevel surgery (MLS) has become one of the most preferred surgical methods for the treatment of obstructive sleep apnea syndrome (OSAS). In this study, we aimed to present our results for MLS together with modified expansion sphincter pharyngoplasty (MESP) for the treatment of OSAS. We also investigated whether performing anteriorpalatoplasty (AP) affected surgical results in these patients. Methods: Fifty patients diagnosed with moderate-to-severe OSAS after polysomnography (PSG) were prospectively included in the study. The patients underwent MLS comprising; nasal surgery, MESP, and ablation of the tongue base with radiofrequency. In addition, AP was performed in 30 patients. Surgical success was determined using PSG data and Epworth sleepiness scale (ESS) scoring performed before and after surgery. Results: There was a statistically significant improvement in ESS scores and postoperative PSG findings compared with preoperative means (p<0.001). Surgical success was achieved in 40 patients (80%) according to the Sher criteria. Surgical success ratio revealed exactly same (p=1.000) compared with the patients who were not performed AP. Preoperative apnea index, apnea/hypopnea index (AHI), and supine AHI were significantly higher in surgically unsuccessful cases (p<0.05). Conclusion: MLS, including MESP, performed together with nasal surgery and tongue base RF is an alternative procedure in the surgical treatment of OSAS with a postoperative success rate of 80%, according to our study results. In addition to MESP, AP may not affect the results of multilevel surgery.